Master students’ perception on plagiarism during research writing in faculty of education - Augustine, Sandra Eberechukwu; Opara, Elvis Chimobi (Universitas Mercu Buana Yogyakarta, 2024)
The study was on master students’ perception on plagiarism during research writing in the Faculty of Education. This study answered and tested four research questions and six hypotheses at a 0.05 significant level. The study used Imo State University (IMSU) and the University of Port Harcourt (UPH), a descriptive survey design, 276 master students’ population, and a sample size of 95 students drawn through a stratified random sampling technique. The instrument was a 37-item Questionnaire on Ethical Issues and Plagiarism in the Faculty of Education (QETPFE) with a 0.85 reliability index. Data analyses were done through the Statistical Package for Social Sciences using mean, standard deviation, percentage, and t-tests. The findings showed that the master’s students in the Faculty of Education at IMSU and UPH have positive perceptions of the ethical rules governing people’s work usage during thesis writing; the perception differed significantly based on gender but was insignificant on an institutional basis. Their plagiarism consequences awareness level was high, irrespective of gender and institution. The male and female students in the Faculty of Education of both universities can paraphrase referenced materials themselves without paying someone for it and use online paraphrasing tools to re-write referenced materials in their theses. The findings implied that female students are more prone to plagiarism than male students. The recommendation, among others, was that postgraduate lecturers emphasize the need for male and female students to adhere strictly to the ethical standards governing other authors’ intellectual property usage. Keywords: Ethical issues, intellectual property, plagiarism, plagiarism checking tools, and research writing.